Short-time kinetics and initial correlations in nonideal quantum systems - Kremp, D.; Semkat, D.; Bornath, Th. (Condensed Matter Physics, 2006)
There are many reasons to consider quantum kinetic equations describing the evolution of a many-particle
system on ultrashort time scales, e. g. correct energy conservation in nonideal plasmas, buildup of correlations
(bound states), and kinetics of ultrafast processes in short-pulse laser plasmas.
We present a quantum kinetic theory including initial correlations and being valid on arbitrary time scales.
Various examples of short-time relaxation processes, such as relaxation of the distribution function and the
energy, are shown. Furthermore, gradient expansions of the general equations and the role of bound states
are discussed. Є багато причин щоб розглядати квантовi кiнетичнi рiвняння, що описують еволюцiю багаточастинкової системи в ультракоротких часових масштабах, наприклад збереження енергiї у неiдеальнiй
плазмi, наростання кореляцiй (зв’язанi стани) та кiнетика ультрашвидких процесiв у короткоiмпульснiй лазернiй плазмi.
Представлено квантову кiнетичну теорiю, що включає початковi кореляцiї та є справедливою на довiльних часових масштабах. Показано рiзнi приклади короткочасових релаксацiйних процесiв, такi
як релаксацiя функцiї розподiлу та енергiї. Крiм того обговорюється градiєнтний розклад загальних
рiвнянь та роль зв’язаних станiв.